Homomorphisms of the algebra of symmetric analytic functions on _1 - Chernega, I.V. (Carpathian Mathematical Publications, 2014)
The algebra H_bs(_1) of symmetric analytic functions of bounded type is investigated. In particular, we study continuity of some homomorphisms of the algebra of symmetric polynomials on _p and composition operators of the algebra of symmetric analytic functions. The paper contains several open questions.